Reweaving the Tundra: Women, Fire, and Fractured Traditions in Anna Nerkagi’s Prose - Gatti Racah, Maria (Matrix, 2026)
Anna Nerkagi (b. 1952), a Nenets writer and cultural activist from the Yamal Peninsula, is one of the few female Indigenous voices in Russophone literature of the North. Beyond her literary work, she has promoted tundra education and the preservation of Nenets culture, exemplifying a form of female creative agency linking literature, education, and cultural stewardship.This article examines her prose through the lens of the relationship between women and the hearth, understood as a central site of ethical, cosmological, and ecological mediation in Nenets life. Focusing on Aniko, Ilir, and White Moss, it reads these works as a loose trilogy structured around shifting configurations of female subjectivity: women at the fire, women displaced from it, and women beyond it.Drawing on close textual analysis and ethnographic research, the article argues that the hearth functions as a living relational centre linking humans, animals, and other-than-human beings. At the same time, Nerkagi's narratives register the disruptions brought by Soviet modernity, particularly through boarding schools and the erosion of female genealogies. Rather than opposing tradition and modernity, her works show how Nenets matricultural systems persist through women's labour and ritual authority, allowing the tundra's social and cosmological fabric to be continuously re-woven.